2002
DOI: 10.1016/s0304-3959(01)00388-8
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid injections for lateral epicondylitis: a systematic review

Abstract: Patients with lateral epicondylitis (tennis elbow) are frequently treated with corticosteroid injections, in order to relieve pain and diminish disability. The objective of this review was to evaluate the effectiveness of corticosteroid injections for lateral epicondylitis. Randomised controlled trials (RCTs) were identified by a highly sensitive search strategy in six databases in combination with reference tracking. Two independent reviewers selected and assessed the methodological quality of RCTs that inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
143
0
15

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(163 citation statements)
references
References 44 publications
5
143
0
15
Order By: Relevance
“…However, this need for diagnostic refinement is likely to be limited, since the most recent Cochrane reviews have concluded that steroid injections, ultrasound, and acupuncture are of limited or uncertain benefit at the shoulder (15)(16)(17), and that acupuncture is of unproven benefit (19) and shockwave therapy is ineffective (21) for lateral elbow pain. On the other hand, recent non-Cochrane reviews do favor steroid injections over placebo as a treatment for lateral elbow pain with tenderness (25)(26)(27), further supporting the case for distinguishing patients in whom elbow pain is accompanied by tenderness.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, this need for diagnostic refinement is likely to be limited, since the most recent Cochrane reviews have concluded that steroid injections, ultrasound, and acupuncture are of limited or uncertain benefit at the shoulder (15)(16)(17), and that acupuncture is of unproven benefit (19) and shockwave therapy is ineffective (21) for lateral elbow pain. On the other hand, recent non-Cochrane reviews do favor steroid injections over placebo as a treatment for lateral elbow pain with tenderness (25)(26)(27), further supporting the case for distinguishing patients in whom elbow pain is accompanied by tenderness.…”
Section: Discussionmentioning
confidence: 95%
“…For these purposes, we searched in Medline and Embase (from the last relevant Cochrane search date to June 2010) and in Google Scholar (first 300 hits in March 2010), combining terms for upper extremity disorder with those for RCTs. After elimination of duplicate references, these searches yielded 156 potentially relevant articles from Cochrane reviews and 189 other potentially relevant titles (including several that were cited in 4 non-Cochrane reviews [on steroid injections (25)(26)(27) and physiotherapy for epicondylitis (28)]) identified by the search.…”
Section: Methodsmentioning
confidence: 99%
“…Clínicamente se caracteriza por la aparición de dolor a la palpación del cóndilo lateral que se agravan al realizar extensión o supinación de la muñeca contra resistencia. El tratamiento más común consiste en reposo, aplicación de frío en la fase aguda, AINE e infiltración de esteroides en fase de crónica, aunque sin dar una solución rápida y eficaz (1). La radiofrecuencia pulsada aplicada en estos casos, permite el tratamiento local de la zona lesionada favoreciendo la cicatrización y la modulación de la respuesta dolorosa al aplicarla sobre el nervio sensitivo de la zona (nervio cutáneo braquial lateral).…”
Section: Sr Directorunclassified
“…KS se çi mi, doz ve mik ta rı ko nu sun da yi ne ye ter li veri ol ma dı ğı bil di ril miş tir. 25 ELEK TRO TE RA Pİ DI ŞIN DA Kİ TE DA Vİ LER Or tez…”
Section: Kor Ti̇ Kos Te Ro İd (Ks)unclassified
“…KS se çi mi, doz ve mik ta rı ko nu sun da yi ne ye ter li ve ri ol ma dı ğı bil di ril miş tir. 25 Or tez ler ile il gi li mev cut ça lış ma lar da kon trol grup la rı, so nuç öl çüm le ri, kul la nı lan or tez ti pi, yakın ma sü re si, prog nos tik fak tör le rin çe şit li li ği ve dü şük va ka sa yı la rı ne de niy le ke sin so nuç bil di rile me ye ce ği, bun la rın dik ka te alı na rak ya pıl dı ğı ça-lış ma la rın ge rek li li ği bil di ril miş tir. 17 De rin trans vers frik si yon ma sa jı nın et kin li ği ile il gi li ça lış ma lar da ki va ka sa yı sı az lı ğı ne de niy le so nuç çı kar tı la ma ya ca ğı be lir til miş tir.…”
Section: Cer Ra Hi̇unclassified